2014
DOI: 10.4314/ajtcam.v11i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Investigation On Antidiarrhoeal Activity Of <i>Aristolochia Indica</i> Linn. Root Extracts In Mice

Abstract: Background: The present study aimed at investigating the effect of ethanolic extract (EtAI), and aqueous extract (AqAI) of Aristolochia indica Linn roots on castor oil-induced diarrhoea and study on small intestinal transit. Phytochemical analysis of extracts was performed as per standard procedure. Materials and Methods:The oral toxicity study using Swiss albino mice was performed in accordance with OECD guidelines. The EtAI and AqAI extracts of Aristolochia indica Linn were studied for antidiarrhoeal propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The assays, however, showed that this had moderate antibacterial activities across all bacterial samples tested here (Fig 2). In agreement with this, the antidiarrheal properties of A. indica [48], C. odorata [26], M. charantia [32] and A. ringens [49] have been reported elsewhere.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…The assays, however, showed that this had moderate antibacterial activities across all bacterial samples tested here (Fig 2). In agreement with this, the antidiarrheal properties of A. indica [48], C. odorata [26], M. charantia [32] and A. ringens [49] have been reported elsewhere.…”
Section: Plos Onesupporting
confidence: 83%
“…The primary healthcare facilities investigated in this study did not carry out laboratory diagnosis of reported cases of AGE or follow up the patients. Previous studies, using castor oil-induced diarrhoea in Wistar rats, have reported antidiarrheal properties of a number of herbal extracts [ 26 , 30 , 32 , 48 50 ]. Therefore, we chose to investigate the antibacterial properties of selected plants, which were major ingredients of herbal medication reported as used in the management of AGE.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-diarrhoeal activity of A. indica ethanol and aqueous root extract tested in castor oil-induced diarrhoea male Swiss albino mice resulted the inhibition of 72.38% and 61.94% at a higher dose level 400 mg/kg as compared with diphenoxylate HCl. A delay of the intestinal transit in charcoal meal-induced mice was recorded at the doses of 200 mg/kg and 400 mg/kg of plant extract confirmed the significant result in charcoal induced gastrointestinal motility test (Dharmalingama et al, 2014).…”
Section: Anti-diarrhoeal Activitysupporting
confidence: 63%
“…It has been experimentally shown that the plant several various bioactivities such as antimicrobial (Shafi et al, 2002;Umamaheshwari & Muthy, 2012;Venkateswarlu et al, 2013), antioxidant (Thirugnanasampandan et al, 2008;Hossen et al, 2014), inhibition of drug induced hyperuricemia (Ramachandran et al, 2008), anthelmintic (Mini et al, 2013), antihyperglycemic (Shanmugam et al, 2014), antidiarrheal (Dharmalingam et al, 2014), antiinflammatory (Mathew et al, 2011), antipruritic (Mathew et al, 2011), mast cell stabilizing (Mathew et al, 2011) and immunomodulatory (Mallaiah et al, 2015) activity. In the present study, we determined antimicrobial and radical scavenging efficacy of leaf and flower extract of A. indica.…”
Section: Original Researchmentioning
confidence: 99%